2015
DOI: 10.7150/ijms.10144
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Detection of Circulating Nucleophosmin Mutations DNA in the Plasma of Patients with Acute Myeloid Leukemia

Abstract: Objective: The aim of this study was to quantify the copies of circulating nucleophosmin (NPM) mutations DNA in the plasma of patients with acute myeloid leukemia (AML) and to explore the association of circulating NPM mutation levels with clinical characteristics.Design and Methods: The presence of NPM mutations in 100 Chinese patients newly diagnosed with AML were identified by RT-PCR and sequencing analysis. Copies of circulating NPM mutation A (NPM mut.A) DNA in the plasma of mutation-positive cases were q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 22 publications
2
14
0
2
Order By: Relevance
“…Mutation of NPM1 gene was identified in 37 of 100 patients using plasma cfDNA, but only in 35 patients using PB cells. It was found that copies of NPM1 mutations in PB were significantly associated with different subtypes of AML and also with higher white blood cells count, platelets, and percentage of blast cells in BM …”
Section: Myeloid Malignanciessupporting
confidence: 55%
See 3 more Smart Citations
“…Mutation of NPM1 gene was identified in 37 of 100 patients using plasma cfDNA, but only in 35 patients using PB cells. It was found that copies of NPM1 mutations in PB were significantly associated with different subtypes of AML and also with higher white blood cells count, platelets, and percentage of blast cells in BM …”
Section: Myeloid Malignanciessupporting
confidence: 55%
“…The first study dealing with analysis of cfDNA in hematological malignancies, especially in MDS and AML, was published in 1994 . Since then, a few studies on cfDNA in hematological malignancies showed that cfDNA derived from tumor cells is potentially useful for diagnosis, prognosis, monitoring of tumor burden, and response to treatment . Most of these studies focused on lymphoid malignancies, especially those derived from B cells.…”
Section: Use Of Cfdna In Hematological Malignanciesmentioning
confidence: 99%
See 2 more Smart Citations
“…Cytogenetics and specific molecular profiles (NPM1, c-Kit, FLT3, CEBPA) in AML are used to define prognosis and guide treatment decisions following induction 23 . It has been shown in a recently published study that NPM mutations can be detected and quantified in the PB 24 at a rate commensurate with the rate of detection in historical BM samples 25 . However, this study did not report parallel assessment of NPM mutations in paired cfDNA with BM samples and consequently conclusions about the sensitivity of cfDNA detection could not be drawn.…”
Section: Acute Myeloid Leukaemia (Aml)mentioning
confidence: 75%